Prospective risk assessment of medicine shortages in Europe and Israel: findings and implications - Miljković, Nenad; Hoppe-Tichy, Torsten (Frontiers in pharmacology, 2020)
Abstract Introduction While medicine shortages are complex, their mitigation is more of a challenge. Prospective risk assessment as a means to mitigate possible shortages, has yet to be applied equally across healthcare settings. The aims of this study have been to: 1) gain insight into risk-prevention against possible medicine shortages among healthcare experts; 2) review existing strategies for minimizing patient-health risks through applied risk assessment; and 3) learn from experiences related to application in practice. Methodology A semi-structured questionnaire focusing on medicine shortages was distributed electronically to members of the COST Action 15105 (28 member countries) and to hospital pharmacists of the European Association of Hospital Pharmacists (EAHP) (including associated healthcare professionals). Their answers were subjected to both qualitative and quantitative analysis (Microsoft Office Excel 2010 and IBM SPSS Statistics®) with descriptive statistics based on the distribution of responses. Their proportional difference was tested by the Chi-square test and Fisher's exact test for independence. Differences in the observed ordinal variables were tested by the Mann-Whitney or Kruskal-Wallis test. The qualitative data were tabulated and recombined with the quantitative data to observe, uncover and interpret meanings and patterns. Results The participants (61.7%) are aware of the use of risk assessment procedures as a coping strategy for medicine shortages, and named the particular risk assessment procedure they are familiar with: Failure Mode and Effect Analysis (FMEA) (26.4%), Root Cause Analysis (RCA) (23.5%), the Healthcare FMEA (HFMEA) (14.7%) and the Hazard Analysis and Critical Control Point (HACCP) (14.7%). Only 29.4% report risk assessment as integrated into mitigation strategy protocols. Risk assessment is typically conducted within multidisciplinary teams (35.3%). Whereas 14.7% participants were aware of legislation stipulating risk assessment implementation in shortages, 88.2% claimed to not have reported their findings to their respective official institutions. 85.3% consider risk assessment a useful mitigation strategy. Conclusion The study indicates a lack of prospective, systematically organized tools used to analyze clinical as well as operationalized risk stemming from medicine shortages in healthcare. There is also a lack of legal instruments and sufficient data confirming the necessity and usefulness of risk assessment in mitigating medicine shortages in Europe
Gesehen am 18.05.2020